EClinic: increasing use of telehealth as a risk reduction strategy during the covid-19 pandemic. Issue 1 (16th April 2020) - Kemp, Michael T; Williams, Aaron M; Alam, Hasan B
Abstract : Prior to the covid-19 pandemic, telehealth was already being rapidly adopted nationally by healthcare systems. During the covid-19 pandemic, increased use of telehealth may be considered as a risk reduction strategy. Benefits of this strategy may be conferred to both patients and health providers.